The cost-effectiveness of antibiotic-loaded bone cement versus plain bone cement following total and partial knee and hip arthroplasty - Hoskins, Tyler (J Orthop, 2020)
BACKGROUND: Postoperative infection is one of the most prevalent complications following total joint arthroplasty (TJA). As such procedures become more prevalent, it is imperative that we develop new prophylactic methods to prevent the need for revision procedures. In recent years, surgeons have opted to use antibiotic-loaded bone cement (ALBC) rather than plain bone cement (PBC) in primary hip and knee replacements due to its theoretical potential of lowering infection rates. However, the cost-effectiveness of this intervention remains in question. Questions/Purposes: To determine the rate of infection and cost-effectiveness of antibiotic-loaded bone cement as compared to plain bone cement in hip and knee arthroplasty. PATIENTS AND METHODS: We reviewed 4116 primary hip and knee arthroplasty cases performed between 2016 and 2018 at Morristown Medical Center in New Jersey. Data regarding demographics, complications, and any readmissions due to deep infection were collected retrospectively. During that time period there were a total of 4016 knee cases (423 ALBC, 3593 PBC) and 123 hip cases (63 ALBC, 60 PBC). The average cost for one bag of antibiotic-loaded bone cement and plain bone cement for hip and knee arthroplasty was $336.42 and $72.14, respectively. A statistical analysis was performed using Fisher's exact test; the National Healthcare Safety Network (NHSN) surgical site infection guidelines were used to distinguish between superficial and deep infections. RESULTS: Ten patients were readmitted due to deep infection, all of whom had undergone total knee arthroplasty. Of those cases, plain bone cement was used for the index procedure in seven instances and antibiotic-loaded cement was used in three. This resulted in an infection rate of 0.19% and 0.62%, respectively, p = 0.103. There was no statistically significant difference in infection rates between the two groups. A total of 778 bags of ALBC were used in 423 knee surgeries, and 98 bags of ALBC were used in 63 hip cases. The total cost for ALBC in TKA and THA procedures was $261,734.76 (778*336.42) and $32,969.16 (98*336.42), respectively. If PBC had been used during all index procedures, it would have resulted in a total savings of $231,509.28. CONCLUSIONS: Antibiotic-loaded cement did not significantly reduce the rate of infection for either knee or hip arthroplasty. Thus, the routine use of antibiotic-loaded cement in primary hip and knee arthroplasty may be an unnecessary financial burden to the healthcare system. A larger sample size and a randomized controlled trial would help confirm our findings and would provide further information on the cost-effectiveness of ALBC cement versus PBC. Significance/Clinical Relevance: In this review of cases performed from 2016 to 2018 there was no statistically significant difference between the rate of infection and the need for revision surgeries for patients treated with ALBC versus PBC. As hospital systems continue to transition towards a bundled payment model, it becomes imperative for providers to reduce any unnecessary costs in order to increase quality and efficiency. We estimate that our hospital system could save nearly $120,000/year by using plain bone cement instead of antibiotic-loaded cement.